2013
DOI: 10.2190/pm.45.3.f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between the Znf804A Single Nucleotide Polymorphism Rs1344706 a/c Variant and Schizophrenia Subtype in Han Chinese Patients

Abstract: We found no evidence that the ZNF804A SNP rs1344706 is a susceptibility locus for SZ. However, conflicting results from previous association studies may be due to genetic heterogeneity between different patient SZ subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Some have provided strong support for susceptibility variants in ZNF804A in schizophrenia or bipolar disorder Riley et al, 2010;Sazci et al, 2012;Schwab et al, 2013;Williams et al, 2011;Xiao et al, 2011;Yang et al, 2013;Zhang et al, 2011a), whereas others have shown a negative association (Landaas et al, 2011;Li et al, 2011;Liou et al, 2012;Thurin et al, 2013;Zaharie et al, 2012). These differences may be caused by the type of disease, ethnicity, or sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Some have provided strong support for susceptibility variants in ZNF804A in schizophrenia or bipolar disorder Riley et al, 2010;Sazci et al, 2012;Schwab et al, 2013;Williams et al, 2011;Xiao et al, 2011;Yang et al, 2013;Zhang et al, 2011a), whereas others have shown a negative association (Landaas et al, 2011;Li et al, 2011;Liou et al, 2012;Thurin et al, 2013;Zaharie et al, 2012). These differences may be caused by the type of disease, ethnicity, or sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our meta-analyses indicated significant association of rs1344706 with schizophrenia in Northern Chinese populations ( P  = 0.005, OR = 1.09, 95% CI 1.03–1.15), i.e ., Shanxi, Xinxiang and Shandong121314, which was inconsistent with most studies conducted in either Central or Southern Chinese populations, including Jiangsu, Yunnan, Sichuan and Guangxi province15161718. This inconsistence may originate from the following several reasons.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the MAF of rs1344706 in controls was slightly different among Northern (0.489)13, Central (0.41)9 and Southern (0.491)15 Chinese populations, which might cause between-study heterogeneity. Therefore, we conducted meta-analysis using studies from northern, central, and southern China respectively.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations